Factor Affecting the Completeness of Chlinical Pathway Filling by Doctors at Hospital Abepura Papua Province - Monalisa A. Manufandu; Hasmi; Sarce Makaba; Novita Medyati; Agus Zainuri, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2024)
Clinical pathway as hospital law becomes a reference or standard for medical services from the time the patient arrives until the patient leaves the hospital so that doctors are obliged to carry out complete documentation as hospital law and the amount of costs for patients in managing hospital management. Initial observations at the Abepura Regional Hospital found that several clinical pathway documentation had not been completed completely by the doctor responsible for the service. The aim of the research is to determine the factors that influence the completeness of clinical pathway filling by doctors at the Abepura Regional Hospital Papuan Province. This type of quantitative research uses a cross sectional study approach. The research population was 41 doctors and the sample studied was 32 Doctors Responsible for Services which was carried out at the Abepura Regional Hospital in January 2024. Data was obtained using questionnaires and clinical pathway documentation data. Data were analyzed using chi square and binary logistic regression. The research results showed that factors that had a significant influence on the completeness of clinical pathway filling by doctors at Abepura Hospital were training (p value 0.018; RP = 3.080 CI 95% (1.289-7.358) and motivation (p value 0.049; RP = 2.556 CI 95% (1.116-5.853). Factors that did not have a significant effect were age (p value 0,433; RP = 0,667 CI95% (0,273-1,631), gender (p value 0.581 or p > ? (0.05); RP = 0.643 CI95% ( 0.242-1.706), employee status (p value 0.338; RP = 1.800 CI 95% (0.737-4.395), length of work (p value 0.165; RP = 2.167 CI95% (0.0.966-4.860), workload (p value 0.073 ; RP = 2.551 CI 95% (1.165-5.587) and knowledge (p value 0.522; RP = 1.587 CI 95% (0.636-3.957). Training is the dominant factor completing the clinical pathway (p value 0.016; OR = 7.933 95% CI (1.478-42.581).Based on the results of this study, it is recommended that the hospital hold training related to filling out chlinical pathway documents every year. In addition, there needs to be rewards & punishments related to filling out medical record documents and the need for regular evaluation and monitoring by the medical record unit of incomplete filling of chlinical pathway documents.